Correlates and consequences of women's participation in the cowpea value chain in eastern Zambia. Issue 3 (3rd July 2017) - Gondwe, Therese; Tegbaru, A.; Oladeji, Alamu E.; Khonje, Makaiko; Manda, J.; Gaya, H.
ABSTRACT: This paper analyses the link between gender differences and different activities along the cowpea value chain as well as food security and asset-based poverty using a recent cross-sectional data set of over 120 farm households in Eastern Zambia. We used the endogenous switching probit regression model to account for both observed and unobserved heterogeneity. Results show that women's participation in the cowpea value chain significantly increases cowpea production, marketing and adoption of improved cowpea varieties. It also reduces both food insecurity and poverty. However, women's participation in the value chain is limited by low levels of education, access to extension, credit, village markets, and improved agricultural technologies. Policies to address these constraints that limit women's participation in the cowpea value chain have the potential to reduce gender disparities, food insecurity, and poverty.